Arsitektur Indis dan Perubahan Sejarah Kota Magelang 1906-1942 - Adyt Alkautsar; La Ode Rabani (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
This study discusses the architecture of Indische buildings at Magelang Town in 1906-1942. This study uses historical research methods consisting of heuristics, source verification, data interpretation and historiography. The entry and development of Indische architecture in Magelang Town coincided with the increasingly intensive colonial government in exploiting natural resources in order to increase commodity exports. This building with Indische architecture in Magelang Town developed from 1906 to 1942 along with the fulfillment of the facilities and needs of the Dutch people who were intensively running the bureaucracy in Magelang Town. The facilities and needs referred to are infrastructure, especially housing, offices, and defense as illustrated in residential buildings, schools, lodging, hospitals, and other public facilities. In 1942, Indische architecture no longer developed in line with the end of Dutch rule in the Dutch East Indies. However, some of the Indische buildings in Magelang Town are still maintained by the community.